2019
DOI: 10.1155/2019/2871289
|View full text |Cite
|
Sign up to set email alerts
|

Glycopatterns and Glycoproteins Changes in MCN and SCN: A Prospective Cohort Study

Abstract: Background. Advances in imaging improve the detection of malignant pancreatic cystic including mucinous cystic neoplasm (MCN), intraductal papillary mucinous neoplasm (IPMN), and mucinous cystic adenocarcinoma (MCA), but the distinction between benign and malignant lesions remains a problem. In an effort to establish glycopatterns as potential biomarkers for differential diagnosis between MCN and SCN, we systematically investigated the alterations of glycopatterns in cystic fluids for both SCN and MCN. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…As reported, the immune complement system was involved in mucinous cystic neoplasm (MCN), combined with their performance in this study, it supported the inference that the similarity between cancer and RA [ 82 ]. Moreover, with the help of KOG analysis, this inference got more supported.…”
Section: Discussionsupporting
confidence: 87%
“…As reported, the immune complement system was involved in mucinous cystic neoplasm (MCN), combined with their performance in this study, it supported the inference that the similarity between cancer and RA [ 82 ]. Moreover, with the help of KOG analysis, this inference got more supported.…”
Section: Discussionsupporting
confidence: 87%
“…It is a potential biomarker of HCC in HCV-infected alcoholic patients. 25 Interestingly, Wang et al found that the elevated expression of FGA, FGG, and SERPING1 activates the immune complement system pathway, 26 which is consistent with the decreased expression levels of all three proteins in the ESS model group. Thus, downregulation of FGA, FGG, and SERPING1 inhibits the complement system and lowers production of complement proteins like C3, resulting in autoimmune activation (Figure 10).…”
Section: Experimental Validationmentioning
confidence: 69%
“…Fibrinogen is a protein with coagulative functions and is mainly synthesized by liver cells; it represents the highest coagulation factor in the plasma and is one of the primary components of blood coagulation. It is converted into fibrin through thrombin catalysis processes occurring in the circulatory system, initiating coagulation and physiological hemostasis functions, which are the primary defense reactions during direct exposure of blood to the external environment [26,27]. Three peptide chains of fibrinogen are respectively encoded by three independent genes: FGA, FGB and FGG [28,29].…”
Section: Discussionmentioning
confidence: 99%